The State of Glossaries of Terms in Library and Information Science in Telugu - Raju, A. A. N. (Journal of Information and Knowledge, 2014)
This paper briefly deals with the efforts, which have been made in the past for the preparation of glossaries of terms for introduction of Telugu as official language at various levels of State administration in Andhra Pradesh. Stresses the need for gio'ssaries in Library and Information Science in Telugu and briefly presents the activities of the institutions like Telugu Akademi in bringing out bilingual glossaries from English to Telugu. The efforts of individuals in bringing out Library and Information Science glossaries in Telugu are also mentioned with examples. The need for more glossaries in the emerging fields of information and communication technologies and support and encouragement for institutions and individuals engaged in the preparation of such glossaries in LIS in Telugu is emphasised.